Calculations for electron-impact excitation and ionization of beryllium. (18th November 2016) - Zatsarinny, Oleg; Bartschat, Klaus; Fursa, Dmitry V; Bray, Igor
Abstract: The B -spline R -matrix and the convergent close-coupling methods are used to study electron collisions with neutral beryllium over an energy range from threshold to 100 eV. Coupling to the target continuum significantly affects the results for transitions from the ground state, but to a lesser extent the strong transitions between excited states. Cross sections are presented for selected transitions between low-lying physical bound states of beryllium, as well as for elastic scattering, momentum transfer, and ionization. The present cross sections for transitions from the ground state from the two methods are in excellent agreement with each other, and also with other available results based on nonperturbative convergent pseudostate and time-dependent close-coupling models. The elastic cross section at low energies is dominated by a prominent shape resonance. The ionization from the ( 2 s 2 p ) 3 P and ( 2 s 2 p ) 1 P states strongly depends on the respective term. The current predictions represent an extensive set of electron scattering data for neutral beryllium, which should be sufficient for most modeling applications.